Anti-static and anti-precipitation PVC foam product and preparation method thereof

By using raw materials such as ethylene-vinyl alcohol copolymer, calcium-zinc stabilizer, composite foaming agent and nano silver oxide in PVC foamed products, the problems of plasticizer precipitation and electrostatic accumulation are solved, and the anti-plasticizer precipitation, anti-static and good mechanical properties of PVC foamed products are achieved.

CN118374106BActive Publication Date: 2025-03-07HUIZHOU WEIKANG NEW BUILDING MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410428756.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2025-03-07
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

During use, existing PVC materials are prone to surface aging, brittleness, cracking, stickiness and other adverse phenomena due to the precipitation of plasticizers. At the same time, the problem of static electricity accumulation is difficult to effectively solve.

Method used

By adding raw materials such as ethylene-vinyl alcohol copolymer, calcium-zinc stabilizer, composite foaming agent and nano silver oxide to the PVC foaming products, PVC foaming products with anti-plasticizer precipitation and anti-static properties are prepared.

Benefits of technology

It realizes the anti-plasticizer precipitation and anti-static functions of PVC foamed products, and at the same time improves its mechanical properties and has good elasticity and comprehensive performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the field of PVC technology. An anti-static and anti-precipitation PVC foam product comprises the following raw materials by weight: 80 to 120 parts of PVC resin, 10 to 15 parts of ethylene-vinyl alcohol copolymer, 5 to 8 parts of calcium zinc stabilizer, 10 to 45 parts of plasticizer, 15 to 20 parts of composite foaming agent, 6 to 9 parts of foaming regulator, 2 to 3 parts of lubricant, 0.2 to 1 part of antioxidant, and 5 to 10 parts of filler. The PVC foam product of the present invention has the properties of anti-plasticizer precipitation, anti-static and the like, and has good mechanical properties. The present invention also provides a method for preparing an anti-static and anti-precipitation PVC foam product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVC, and in particular relates to an anti-static and anti-precipitation PVC foam product and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) has the characteristics of high strength, acid and alkali corrosion resistance, and flame retardancy. The hardness can be adjusted according to needs, and different soft and hard products can be produced. Although PVC has unique properties and its plastic products are widely used, it is a polymer material that is difficult to process due to its poor thermal stability and easy decomposition when heated. It is difficult to process without formula design. Most of the formula designs require the addition of heat stabilizers and plasticizers to successfully process and shape them into various soft and hard products to adapt to different application fields, such as flooring, daily necessities, building materials, industrial products and many other fields.

[0003] At present, the most commonly used plasticizer in the field of PVC materials is phthalate esters, but many studies have shown that small molecular weight phthalate ester plasticizers are easy to migrate and precipitate to the surface of the blended product, causing the film to age, become brittle, crack, become sticky and other undesirable phenomena, shortening the service life of the blended product. At the same time, the plasticizer will also bring out some components during the precipitation process, such as antistatic agents, stabilizers, etc., and simply adding antistatic agents to achieve the antistatic technical effect is also likely to cause the antistatic properties of PVC products to deteriorate due to the precipitation of antistatic agents, resulting in easy accumulation of static electricity during use. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an anti-static and anti-precipitation PVC foam product, the PVC foam product of the present invention has the properties of anti-plasticizer precipitation, anti-static and the like, and has good mechanical properties. The present invention also provides a preparation method of the anti-static and anti-precipitation PVC foam product.

[0005] The technical solution adopted by the present invention to solve the above problems is as follows:

[0006] An anti-static and anti-precipitation PVC foam product, comprising the following preparation raw materials in parts by weight:

[0007] 80-120 parts of PVC resin, 10-15 parts of ethylene-vinyl alcohol copolymer, 5-8 parts of calcium zinc stabilizer, 10-45 parts of plasticizer, 15-20 parts of composite foaming agent, 6-9 parts of foaming regulator, 2-3 parts of lubricant, 0.2-1 part of antioxidant and 5-10 parts of filler.

[0008] Calcium zinc stabilizer is used to improve the heat resistance and weather resistance of polyvinyl chloride. Azodicarbonamide, as a commonly used foaming agent, has good dispersibility in polymers, fast foaming rate, and is easy to make multiple bubbles converge to form large bubbles, affecting the density and dispersion of the pores. In the process of preparing PVC foam products, a certain amount of ethylene-vinyl alcohol copolymer with excellent barrier properties is mixed into the present invention, which can prevent excessive gas escape during the foaming process, achieve full foaming, improve the density of the internal pores, and greatly reduce the density of the PVC foam products.

[0009] Furthermore, the plasticizer is a phthalate plasticizer.

[0010] Furthermore, the composite foaming agent is composed of the following raw materials in parts by weight: 8 to 15 parts of azodicarbonamide, 0.5 to 3.5 parts of nano silver oxide dispersion, 1 to 3 parts of polyvinyl alcohol fiber, 2 to 3 parts of graphene chloride, and 2.5 to 5 parts of silane coupling agent.

[0011] Polyvinyl alcohol fiber can increase the elasticity and toughness of the material, while playing a role in lubrication and improving fluidity. Chlorinated graphene has good electrical conductivity and mechanical strength.

[0012] Furthermore, the preparation method of the nano silver oxide dispersion is: dispersing the nano silver oxide in anhydrous ethanol, then adding polyvinyl alcohol and polyvinyl pyrrolidone, heating to 60-80° C., dispersing at a speed of 1100 r / min-1300 r / min for 20-50 min while heating, and naturally cooling to room temperature to obtain the nano silver oxide dispersion.

[0013] Furthermore, the particle size of the nano silver oxide is 25 to 35 nm.

[0014] In the above technical scheme, if the particle size of the nano silver oxide used is too large, it is easy to cause the foaming gas to agglomerate, resulting in poor uniformity and density of the pores, thereby affecting the mechanical properties of the PVC foamed product; the nano silver oxide with a particle size of 25 to 35 nm is selected, which is easy to adsorb on the foaming gas and form an electrostatic conductive network with graphene chloride and polyvinyl alcohol fiber in the blended material, thereby increasing the electrostatic conductive performance and making the PVC foamed product have an anti-static function.

[0015] Furthermore, the mass ratio of the nano silver oxide, the polyvinyl alcohol and the polyvinyl pyrrolidone is 2-5:3-7:7.

[0016] In the above technical scheme, the surface of nano silver oxide is coated and modified with polyvinyl alcohol and polyvinyl pyrrolidone to ensure that the nano silver oxide particles are stably and evenly dispersed in the system. The particle size of nano silver oxide and the dosage ratio of nano silver oxide to polyvinyl alcohol and polyvinyl pyrrolidone have a great influence on whether the dispersion can be evenly dispersed and whether good stability can be obtained. The researchers found that nano silver oxide with a particle size of 25 to 35 nm is compounded with polyvinyl alcohol and polyvinyl pyrrolidone in a mass ratio of 2 to 5:3 to 7:7, and the obtained dispersion is evenly dispersed and has good stability. In the foaming process of preparing PVC foam products, a stable and uniform dispersion is conducive to controlling the size and uniformity of the pores, making the bubbles more stable and not easy to break, and contributing to the formation and stability of the pores.

[0017] Furthermore, the chlorine content in the chlorinated graphene is 35wt%.

[0018] Furthermore, the preparation method of the composite foaming agent is: adding 8 to 15 parts of azodicarbonamide, 0.5 to 3.5 parts of nano silver oxide dispersion, 1 to 3 parts of polyvinyl alcohol fiber, 2 to 3 parts of graphene chloride, and 2.5 to 5 parts of silane coupling agent, and mixing at 60 to 80° C. for 15 to 20 minutes.

[0019] In the above technical scheme, the silane coupling agent can improve the bonding ability between inorganic and organic substances. Adding the silane coupling agent to the composite foaming agent is beneficial to promoting the coupling between the nano silver oxide dispersion, graphene chloride, and polyvinyl alcohol fiber in the composite foaming agent, enhancing the bonding force between the nano silver oxide and the graphene chloride and polyvinyl alcohol fiber, while improving the compatibility with the PVC material and reducing the precipitation and uneven dispersion phenomenon; after foaming, the graphene chloride and polyvinyl alcohol fiber play a supporting role, which can prevent the bubble from bursting and effectively improve the stability and strength of the pores.

[0020] Furthermore, the foaming regulator is an acrylate foaming regulator.

[0021] Furthermore, the lubricant is one or more of stearic acid, paraffin, polyethylene wax, and monoglyceride.

[0022] Furthermore, the antioxidant is at least one of antioxidant 1010, antioxidant 264, and antioxidant 1076.

[0023] Furthermore, the filler is one or more of calcium carbonate, titanium dioxide, wollastonite, and bentonite.

[0024] The present invention also provides a method for preparing an anti-static and anti-precipitation PVC foam product, comprising the following steps:

[0025] S1. Add PVC resin, calcium zinc stabilizer, lubricant, antioxidant and filler into a hot mixer by weight and mix at 800r / min~1200r / min for 8~15min;

[0026] S2. Then add ethylene-vinyl alcohol copolymer, plasticizer, composite foaming agent, foaming regulator in parts by weight, mix at 110 ℃ ~ 130 ℃ at 600r / min ~ 800r / min for 5 to 30min to obtain a pre-foamed blended material;

[0027] S3. The pre-foamed blended material is fed into a foaming mold groove for compression foaming. In the mold groove, the compression foaming temperature is 170°C to 230°C, the pressure is 5 to 20 MPa, and the foaming time is 5 to 30 min.

[0028] The present invention has the following beneficial effects:

[0029] The composite foaming agent prepared by the invention has good foaming uniformity, dispersibility and stability, can effectively reduce the bubble bursting phenomenon, effectively improve the stability and strength of the foam holes, and improve the foaming effect; at the same time, the dense and uniform foam holes are also conducive to the dispersion of the plasticizer in the PVC mixed matrix; the composite foaming agent has good compatibility with other materials, can reduce the precipitation and uneven dispersion phenomena; the electrostatic conductive network formed by the graphene chloride, the polyvinyl alcohol fiber and the nano silver oxide in the PVC foam product enables the PVC foam product to have an antistatic function, and at the same time improves the mechanical properties of the PVC foam product, and has good elasticity and comprehensive performance.

[0030] The PVC foamed product of the invention has the properties of anti-plasticizer precipitation, anti-static properties and the like, and also has good mechanical properties. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are not limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Unless otherwise specified, the test materials, reagents, methods and equipment used in the following examples are conventional test materials, reagents, methods and equipment in the technical field; unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources. The quantitative tests in the following examples were all repeated three times, and the data are the average or average ± standard deviation of the three repeated experiments.

[0033] Examples 1 to 5 respectively provide an anti-static and anti-precipitation PVC foam product, the component contents are shown in Table 1, and the preparation method is as follows:

[0034] S1. Add PVC resin, calcium zinc stabilizer, lubricant, antioxidant and filler to a hot mixer in parts by weight and mix at 1000r / min for 12min;

[0035] S2. Then add ethylene-vinyl alcohol copolymer, plasticizer, composite foaming agent, foaming regulator in parts by weight, mix at 130 ° C at 800r / min for 20min to obtain a pre-foamed blend material;

[0036] S3. The pre-foamed blended material is fed into the foaming mold groove for compression foaming. In the mold groove, the compression foaming temperature is 220° C., the pressure is 10 MPa, and the foaming time is 20 min.

[0037] Specifically, the steps of preparing the composite foaming agent are: adding 10 parts of azodicarbonamide, 2 parts of nano silver oxide dispersion A, 1.5 parts of polyvinyl alcohol fiber, 2.5 parts of graphene chloride, and 4 parts of silane coupling agent, and mixing at 75° C. for 20 minutes.

[0038] Specifically, the chlorine content in the chlorinated graphene is 35wt%.

[0039] Specifically, the steps of preparing the nano silver oxide dispersion A are as follows: 35 parts by weight of nano silver oxide (30 nm) are dispersed in anhydrous ethanol, then 16 parts by weight of polyvinyl alcohol and 49 parts by weight of polyvinyl pyrrolidone are added, heated to 60-80° C., dispersed at a speed of 1200 r / min for 30 min while heating, and naturally cooled to room temperature to obtain the nano silver oxide dispersion A.

[0040] Specifically, the silane coupling agent is selected as γ-aminopropyltriethoxysilane.

[0041] Table 1: Component contents of PVC foam products of Examples 1 to 3 (unit: parts by weight)

[0042] Preparation of raw materials Example 1 Example 2 Example 3 PVC resin 100 110 115 Ethylene-vinyl alcohol copolymer 12 13 11 Calcium zinc stabilizer 5 5 5 Dioctyl phthalate 36 28 33 Composite foaming agent 19 18 20 ACR foaming regulator 7 7 8 Polyethylene wax 2 2 2 Antioxidant 1010 0.8 0.6 0.5 Titanium dioxide 5 4 3 Wollastonite 2.5 4 5

[0043] Comparative Example 1

[0044] A PVC foam product, which is different from Example 1 in that ethylene-vinyl alcohol copolymer is not added.

[0045] Comparative Example 2

[0046] A PVC foam product, which differs from Example 1 in that only 19 parts by weight of azodicarbonamide is added, and no composite foaming agent is added. Other preparation methods can be obtained in the same way.

[0047] Comparative Example 3

[0048] A PVC foam product, which is different from Example 1 in that no silane coupling agent is added in the preparation of the composite foaming agent, and other preparation methods can be obtained in the same way.

[0049] Comparative Example 4

[0050] A PVC foam product, which is different from Example 1 in that no polyvinyl alcohol fiber is added in the preparation of the composite foaming agent, and other preparation methods can be obtained in the same way.

[0051] Comparative Example 5

[0052] A PVC foam product, which differs from Example 1 in that: the nano silver oxide dispersion A is replaced by the nano silver oxide dispersion B;

[0053] Specifically, the steps of preparing the nano silver oxide dispersion B are as follows: 35 parts by weight of nano silver oxide (80 nm) are dispersed in anhydrous ethanol, then 16 parts by weight of polyvinyl alcohol and 49 parts by weight of polyvinyl pyrrolidone are added, heated to 60-80° C., dispersed at a speed of 1200 r / min for 30 min while heating, and naturally cooled to room temperature to obtain the nano silver oxide dispersion B.

[0054] The performance of the PVC foam products prepared in the above examples and comparative examples was tested. The test results are shown in Tables 2 and 3.

[0055] Table 2: Test results of the embodiments

[0056] Test Project Test Standards Example 1 Example 2 Example 3 Surface resistivity / Ω GB / T 1410-2006 <![CDATA[4.3×10 6 ]]> <![CDATA[4.8×10 6 ]]> <![CDATA[4.5×10 6 ]]> Plasticizer migration and precipitation rate / % HG / T 4454-2012 0.6 0.7 0.6 Bending strength / MPa GB / T9341-2000 43.6 42.1 42.5 Impact strength / (KJ / m2) GB / T9341-2000 20.5 19.6 21.7 Tensile strength / MPa GB / T 1040.3-2006 35.6 32.8 34.1 Elongation at break GB / T 1040.3-2006 315 304 312

[0057] Table 3: Test results of comparative examples

[0058] Test Project Test Standards Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Surface resistivity / Ω GB / T 1410-2006 <![CDATA[6.8×10 6 ]]> <![CDATA[5.3×10 8 ]]> <![CDATA[4.7×10 7 ]]> <![CDATA[5.1×10 6 ]]> <![CDATA[2.9×10 9 ]]> Plasticizer migration and precipitation rate / % HG / T 4454-2012 3.5 5.4 2.9 2.8 3.2 Bending strength / MPa GB / T9341-2000 35.7 23.6 14.3 25.6 39.7 Impact strength / (KJ / m2) GB / T9341-2000 16.8 10.4 8.1 12.4 17.8 Tensile strength / MPa GB / T 1040.3-2006 30.4 12.3 15.6 19.5 32.2 Elongation at break GB / T 1040.3-2006 290 298 263 278 301

[0059] The composite foaming agent prepared by the invention has good foaming uniformity, dispersibility and stability, can effectively reduce the bubble bursting phenomenon, effectively improve the stability and strength of the foam holes, and improve the foaming effect; at the same time, the dense and uniform foam holes are also conducive to the dispersion of the plasticizer in the PVC mixed matrix; the composite foaming agent has good compatibility with other materials, can reduce the precipitation and uneven dispersion phenomena; the electrostatic conductive network formed by the graphene chloride, the polyvinyl alcohol fiber and the nano silver oxide in the PVC foam product enables the PVC foam product to have an antistatic function, and at the same time improves the mechanical properties of the PVC foam product, and has good elasticity and comprehensive performance.

[0060] The PVC foamed product of the invention has the properties of anti-plasticizer precipitation, anti-static properties and the like, and also has good mechanical properties.

[0061] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0062] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0063] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An anti-static and anti-precipitation PVC foam product, characterized in that: The preparation comprises the following raw materials by weight: 80-120 parts of PVC resin, 10-15 parts of ethylene-vinyl alcohol copolymer, 5-8 parts of calcium zinc stabilizer, 10-45 parts of phthalate plasticizer, 15-20 parts of composite foaming agent, 6-9 parts of foaming regulator, 2-3 parts of lubricant, 0.2-1 parts of antioxidant, 5-10 parts of filler; The composite foaming agent is composed of the following raw materials in parts by weight: 8 to 15 parts of azodicarbonamide, 0.5 to 3.5 parts of nano silver oxide dispersion, 1 to 3 parts of polyvinyl alcohol fiber, 2 to 3 parts of graphene chloride, and 2.5 to 5 parts of silane coupling agent; The preparation method of the nano silver oxide dispersion is as follows: dispersing the nano silver oxide in anhydrous ethanol, then adding polyvinyl alcohol and polyvinyl pyrrolidone, heating to 60-80° C., dispersing at a speed of 1100 r / min-1300 r / min for 20-50 min while heating, and naturally cooling to room temperature to obtain the nano silver oxide dispersion; The particle size of the nano silver oxide is 25 to 35 nm; The mass ratio of the nano silver oxide, the polyvinyl alcohol and the polyvinyl pyrrolidone is 2-5:3-7:7; The preparation method of the composite foaming agent is as follows: adding 8-15 parts of azodicarbonamide, 0.5-3.5 parts of nano silver oxide dispersion, 1-3 parts of polyvinyl alcohol fiber, 2-3 parts of graphene chloride, and 2.5-5 parts of silane coupling agent, and mixing at 60-80° C. for 15-20 minutes.

2. The anti-static and anti-precipitation PVC foam product according to claim 1, characterized in that: The chlorine content in the chlorinated graphene is 35wt%.

3. A method for preparing the antistatic and anti-precipitation PVC foam product according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Add PVC resin, calcium zinc stabilizer, lubricant, antioxidant and filler into a hot mixer by weight and mix at 800r / min~1200r / min for 8~15min; S2. Then add ethylene-vinyl alcohol copolymer, plasticizer, composite foaming agent, foaming regulator in parts by weight, mix at 110 ℃ ~ 130 ℃ at 600r / min ~ 800r / min for 5 to 30min to obtain a pre-foamed blended material; S3. The pre-foamed blended material is fed into a foaming mold groove for compression foaming. In the mold groove, the compression foaming temperature is 170°C to 230°C, the pressure is 5 to 20 MPa, and the foaming time is 5 to 30 min.

Citation Information

Patent Citations

  • Polymer compositions containing colloids of silver salts

    CA2394214A1

  • Antibacterial high-temperature-resistant mat and preparation method thereof

    CN109535738A